Olfactory Sensitivity for the Mammalian Blood Odor Component Trans-4, 5-epoxy-(E)-2-decenal in CD-1 Mice. (March 2017) - Sarrafchi, Amir; Laska, Matthias
Using a conditioning paradigm and an automated olfactometer, we investigated the olfactory sensitivity of CD-1 mice for the mammalian blood odor component trans -4, 5-epoxy-(E)-2-decenal. We found that two of the animals significantly discriminated concentrations down to 3.0 ppt (parts per trillion) from the solvent, and three animals even successfully detected dilutions as low as 0.3 ppt. Intraspecific comparisons between the olfactory detection thresholds obtained here with those obtained in earlier studies with other odorants show that mice are extraordinarily sensitive to this blood odor component. Interspecific comparisons of olfactory detection thresholds show that human subjects are even more sensitive to trans -4, 5-epoxy-(E)-2-decenal than the mice tested here. Both intra- and inter-specific comparisons suggest that neither neuroanatomical properties such as the size of the olfactory epithelium, the total number of olfactory receptor neurons, or the size of olfactory brain structures, nor genetic properties such as the number of functional olfactory receptor genes or the proportion of functional relative to the total number of olfactory receptor genes allow us to reliably predict a species' olfactory sensitivity. In contrast, the results support the notion that the behavioral relevance of an odorant rather than neuroanatomical or genetic properties may determine a species' olfactory sensitivity.